2020
DOI: 10.5811/cpcem.2020.5.47937
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Acute Transverse Myelitis Following Novel Coronavirus Infection

Abstract: Introduction: During the coronavirus disease 2019 (COVID-19) pandemic, emergency providers are not only seeing an increasing number of patients with COVID-19 infections, but also associated complications and sequelae of this viral illness. Case Report: We present the case of a 28-year-old female patient who presented after a confirmed COVID-19 infection with lower back pain, bilateral symmetric upper and lower extremity numbness, and urinary retention. The patient was diagnosed with acute transverse myelitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 6 publications
4
104
0
16
Order By: Relevance
“…They postulated focal myelitis but without MRI imaging or serological confirmation. The second case was in Boston where a 28-year-old female with a history of hypothyroidism and treatment with levothyroxine developed symptoms of productive cough and low-grade temperature followed by acute myelitis 7 days later ( 4 ). In the third case, Munz et al ( 3 ) reported a 60-year-old patient with acute onset moderate spastic paraparesis with retention of urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They postulated focal myelitis but without MRI imaging or serological confirmation. The second case was in Boston where a 28-year-old female with a history of hypothyroidism and treatment with levothyroxine developed symptoms of productive cough and low-grade temperature followed by acute myelitis 7 days later ( 4 ). In the third case, Munz et al ( 3 ) reported a 60-year-old patient with acute onset moderate spastic paraparesis with retention of urine.…”
Section: Discussionmentioning
confidence: 99%
“…However, spinal cord involvement seems to be rare in COVID-19. To our knowledge, only a few case reports have been published (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular • Ischemic stroke [ 23 ] • Ischemic stroke[ 1 ] • Ischemic stroke with large vesselocclusion [ 11 , 24 ] • Intracerebral hemorrhage,subarachnoidhemorrhage [ 25 , 26 ] • CVST [ 27 – 29 ] • PRES [ 30 – 33 ] • Microvascular occlusivedisorder [ 34 ] 3. Immunological • ADEM [ 35 ] • MS like illness [ 35 38 ] • ADEM[ 15 ] • Post infectious ADEM [ 38 , 39 ] • Acute transverse myelitis [ 40 43 ] • Anti-NMDA encephalitis [ 44 ] • Generalized and diaphragmaticmyoclonus [ 45 , 46 ] • Opsoclonus and ocularflutter [ 47 ] 4. Extrapyramidal features • Parkinsonism [ 48 ] • Parkinsonism [ 49 , 50 ] 5.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…None of these cases manifested features related to cerebrum, optic nerve, cerebellar pathways, or brainstem involvement. Three of them developed neurological symptoms in the second week of illness, with the fourth case manifesting on the 3rd day of illness [ 40 43 ]. MRI study revealed longitudinally extensive transverse myelitis involving the entire length of cord in first two [ 40 ], multifocal transverse myelitis in third [ 42 ], and brainstem involvement in the fourth case [ 40 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation